Preserving earth’s flora in the 21st century: climate, biodiversity, and global change factors since the mid-1940s - Mosoh, Dexter Achu; Prakash, Om; Khandel, Ashok Kumar; Vendrame, Wagner A. (Frontiers in Conservation Science, 2024)
Climate change and biodiversity conservation are two of the most urgent challenges of the twenty-first century. Current global climate models indicate that climate-related events will continue to increase in frequency and intensity, leading to severe impacts on ecosystems, particularly plant diversity. Despite the 2015 Paris Agreement, efforts to limit global warming to 1.5 degrees Celsius and secure adequate climate financing remain unsatisfactory. In addition, the National Biodiversity Strategic Action Plans (NBSAPs), a core mechanism of the Convention on Biological Diversity (CBD), have faced issues in implementation at the national level. Many NBSAPs lack clear and measurable biodiversity targets, which limits their effectiveness. This review presents a comprehensive analysis of these urgent issues, highlighting the significant challenges and deficiencies in current climate and biodiversity conservation policies. It evaluates the effectiveness of the Kew conservation strategy as a model for protecting and conserving plant diversity. Furthermore, this review underscores the pivotal role of plant tissue culture (PTC) technology in achieving plant conservation targets within the post-2020 global biodiversity framework. This review strongly supports the post-2020 global biodiversity framework and the integration of PTC into global plant conservation strategies to meet the ambitious 30-by-30 targets. This review also advocates for the establishment of the Kew-Wide Mechanism (KWM) to bolster climate resilience, reduce anthropogenic impacts on plant diversity, revitalize global conservation efforts, and accelerate ecosystem restoration in the face of ongoing climate change. Proposed as a comprehensive approach to plant conservation, the KWM offers a strategic, innovative, and scalable solution as the global economy transitions toward decarbonization.